Frequency of referral to and attendance at a pulmonary rehabilitation programme amongst patients admitted to a tertiary hospital with chronic obstructive pulmonary disease. Issue 7 (23rd September 2013) - Johnston, Kylie; Young, Mary; Grimmer, Karen; Antic, Ral; Frith, Peter
Abstract Background and objective Pulmonary rehabilitation (PR) is recommended in the management of people with chronic obstructive pulmonary disease (COPD), but implementation appears to be low. The aim of this study was to determine the frequency of referral to, and attendance at, PR programmes in a sample of patients with COPD. Methods A cross‐sectional study of patients admitted to a tertiary hospital in South Australia, with a primary diagnosis of COPD between March and November 2011 was conducted. Data were collected from medical records and patient interview. Results From 235 admissions with preliminary coding as COPD, 88 patients had COPD as the primary reason for admission and were potentially eligible for rehabilitation. While 57% had been referred to rehabilitation during their disease course, only 18% had attended and completed at least half the programme. Seven patients had attended in the previous 2 years. Mean percentage predicted forced expiratory volume in 1 s was 42% at the time of referral. During the index admission, discussion of rehabilitation resulting in a referral occurred in 14 cases (16%). No demographic or disease characteristics were associated with referral/no referral; being reviewed by a COPD nurse coordinator during admission increased the likelihood of referral (odds ratio = 18.7, 95% confidence interval: 3.8–91.4). Conclusions PR had been implemented in a small proportion of patients admitted to hospital with an exacerbation of COPD due to gaps in both referral to and subsequent attendance at a programme. Strategies to improve referral to and participation in PR are required.